Antimicrobial activity of clove extracts against food borne pathogens escherichia.coli, salmonella.tyhimurium, staphylococcus. Aureus and listerai .monocytogenes and gc-ms analysis of extracts - BHARATH M R; M.A.AZEEM; KEERTHAN H V (International Journal of Pharma and Bio Sciences, 2017)
The essential oil of flower buds (clove) of Syzygium aromaticum was obtained by soxhlet extraction with water, petroleum ether and ethyl acetate. The extracts were tested for the antimicrobial activity against Gram-positive and Gram-negative bacteria such as Escherichia coli (MTCC433), Salmonella typhimurium (MTCC98), Staphylococcus aureus (MTCC96), and Listeria monocytogenes (MTCC1143). Clove extracts showed antibacterial activity against all tested bacteria with zone inhibition ranged from 10mm-30mm. Antibacterial activity of clove is attributed to high eugenol, caryophyllene and farnesol content. Many components were identified by Gas chromatography-mass spectrometry, major constituents were eugenol, vanillin, humulene, ledol, adamantane derivative, caryophyllene, farnesol, alizarin and these compounds could be used as therapeutic, medicinal and preservative agents.It is concluded that this plant material can be indispensable source for secondary metabolites